The campus as entrepreneurial ecosystem: the University of Chicago - Miller, David J.; Acs, Zoltan J. (Small business economics, 2017)
This paper employs Frederick Jackson Turner's Frontier Thesis of American democracy to construct a framework for understanding the U.S. university campus as an entrepreneurial ecosystem. One question that immediately comes to mind when studying ecosystem performance is what the proper unit of analysis is: the country, the state, the city, the region, or something smaller, like an incubator or accelerator? This paper suggests that the open, innovative American frontier that closed at the end of the twentieth century has reemerged in the entrepreneurial economy on the U.S. campus. The contemporary campus entrepreneurial ecosystem offers the characteristics of Turner's frontier available assets, liberty, and diversity while creating opportunity, and fostering entrepreneurship and innovation. A case study of the University of Chicago explores governance of the campus as an entrepreneurial ecosystem and the output produced by that campus ecosystem.